Mapping the genetic and environmental aetiology of autistic traits in Sweden and the United Kingdom - Zoe E. Reed; Henrik Larsson; Claire M. A. Haworth; Dheeraj Rai; Sebastian Lundström; Angelica Ronald; Abraham Reichenberg; Paul Lichtenstein; Oliver S. P. Davis (Wiley, 2021)
Abstract Background Autistic traits are influenced by both genetic and environmental factors, and are known to vary geographically in prevalence. But to what extent does their aetiology also vary from place to place? Methods We applied a novel spatial approach to data on autistic traits from two large twin studies, the Child and Adolescent Twin Study in Sweden (CATSS; N = 16,677, including 8307 twin pairs) and the Twins Early Development Study in the UK (TEDS; N = 11,594, including 5796 twin pairs), to explore how the influence of nature and nurture on autistic traits varies from place to place. Results We present maps of gene‐ and environment‐ by geography interactions in Sweden and the United Kingdom (UK), showing geographical variation in both genetic and environmental influences across the two countries. In Sweden genetic influences appear higher in the far south and in a band running across the centre of the country. Environmental influences appear greatest in the south and north, with reduced environmental influence across the central band. In the UK genetic influences appear greater in the south, particularly in more central southern areas and the southeast, the Midlands and the north of England. Environmental influences appear greatest in the south and east of the UK, with less influence in the north and the west. Conclusions We hope this systematic approach to identifying aetiological interactions will inspire research to examine a wider range of previously unknown environmental influences on the aetiology of autistic traits. By doing so, we will gain greater understanding of how these environments draw out or mask genetic predisposition and interact with other environmental influences in the development of autistic traits.